ANALYSIS CORELATION BETWEEN TOTAL ORGANIC MATTER (TOM) WITH ABUNDANCE OF VIBRIO SP. BACTERIA IN INTENSIVE CULTIVATION VANNAMEI SHRIMP (Litopenaeus vannamei) - Amalia, Riska; Widodo, Agus; Widodo, Nazran; Yudhantara, Aziz (Jurnal Perikanan Unram, 2025)
Poor water quality conditions in the cultivation media can cause an increase in pathogenic bacteria such as Vibrio sp. which can inhibit shrimp growth. This study was conducted to analyze the relationship between Total Organic Matter (TOM) and the abundance of Vibrio sp. bacteria in shrimp cultivation media. The stages of the study included checking the abundance of bacteria starting from sterilization of tools, media preparation, bacterial inoculation, bacterial calculations and checking TOM using the titration method. The results showed that TOM in the cultivation media increased as the cultivation period progressed. At the beginning of the distribution, the condition of organic matter in the cultivation media showed a low value and the abundance of Vibrio sp. bacteria in the early stages of cultivation was also low. The highest TOM and abundance of Vibrio sp. bacteria occurred in DOC 91 with a total organic matter of 121.68 ppm and a TVC of 7.29 x 103 CFU/ml. while the lowest TOM and abundance of Vibrio sp. bacteria occurred in DOC 1 with a total organic matter of 88.48 ppm and an abundance of 2.5 x 102 Vibrio sp. CFU/ml. The correlation between TOM and the abundance of Vibrio sp. bacteria in the cultivation media shows a positive linear relationship. This study shows that the high content of organic matter in the cultivation media affects the abundance of Vibrio sp. bacteria in the cultivation media. The higher the organic matter in the cultivation media, the abundance of Vibrio sp. bacteria also increases.